2005
DOI: 10.1002/art.20785
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNA inhibition of SPARC attenuates the profibrotic effect of transforming growth factor β1 in cultured normal human fibroblasts

Abstract: Objective. SPARC (secreted protein, acidic and rich in cysteine), or osteonectin, is a matricellular protein. Recently, it was observed to be overexpressed in fibroblasts obtained from the skin of patients with scleroderma, as well as in different tissues from patients with several other fibrotic disorders. Moreover, a genetic polymorphism in SPARC has been associated with susceptibility to scleroderma. Transforming growth factor ␤1 (TGF␤1) is a profibrotic cytokine that stimulates excessive collagen productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 23 publications
3
38
1
Order By: Relevance
“…As previously published, siSPARC treatment significantly reduced TGF-␤ 1 mRNA and protein levels in HSCs (10). As expected, SPARC knockdown also led to downregulation of collagen type I expression in both LX-2 and rat primary cultured HSCs (34,39). Since only a 50% reduction in SPARC levels was observed in SPARC siRNA-treated CFSC-2G cells, downregulation of collagen type I was not significant in this cell line; however, the expression of this ECM protein was decreased when SPARCdeficient CFSC-2G cells were treated with TGF-␤ 1 .…”
Section: Discussionsupporting
confidence: 85%
“…As previously published, siSPARC treatment significantly reduced TGF-␤ 1 mRNA and protein levels in HSCs (10). As expected, SPARC knockdown also led to downregulation of collagen type I expression in both LX-2 and rat primary cultured HSCs (34,39). Since only a 50% reduction in SPARC levels was observed in SPARC siRNA-treated CFSC-2G cells, downregulation of collagen type I was not significant in this cell line; however, the expression of this ECM protein was decreased when SPARCdeficient CFSC-2G cells were treated with TGF-␤ 1 .…”
Section: Discussionsupporting
confidence: 85%
“…In an intratracheal bleomycin model, Strandjord et al (37) showed that collagen accumulation is decreased in SPARC-null mice. Strandjord et al showed a decrease in collagen accumulation in the lungs of SPARC-null mice following bleomycin injury, a finding supported by recent studies such as those of Zhou et al (38) showing that SPARC regulates collagen expression. The bleomycin model in mice clearly does not completely mirror IPF, especially in regard to chronicity and the presence of fibroblastic foci in IPF but not in the bleomycin model.…”
Section: Discussionmentioning
confidence: 64%
“…Similar to SPARC, transforming growth factor- (TGF-) isoforms have been shown to have increased expression in pancreatic cancer; to correlate with increased invasion and decreased survival in late-stage disease; and to have paradoxical effects on pancreatic tumor progression (Pardali and Moustakas, 2007;Truty and Urrutia, 2007). Moreover, TGF- isoforms activate pancreatic stellate cells and increase SPARC expression to induce a desmoplastic response that is characteristic of pancreatic ductal adenocarcinoma (Mahadevan and Von Hoff, 2007;Podhajcer et al, 2008;Zhou et al, 2005). A common occurrence in the metastatic progression of pancreatic carcinoma is epithelial-to-mesenchymal transition (EMT).…”
Section: Discussionmentioning
confidence: 99%